Fundamental Investigations into Metoprolol Tartrate Deposition on Orodispersible Films by Inkjet Printing for Individualised Drug Dosing - Olga Kiefer; Björn Fischer; Jörg Breitkreutz (MDPI AG, 2021)
Individualised medicine is continuously gaining attention in pharmaceutical research. New concepts and manufacturing technologies are required to realise this therapeutic approach. Off-label drugs used in paediatrics, such as metoprolol tartrate (MPT), are potential candidates for innovations in this context. Orodispersible films (ODFs) have been shown as an accepted alternative dosage form during the last years and inkjet printing is traded as seminal technology of precise deposition of active pharmaceutical ingredients (APIs). The objective of this study was to combine both technologies by developing imprinted ODFs based on hypromellose with therapeutically reasonable MPT single doses of 0.35 to 3.5 mg for paediatric use. After preselection, suitable ink compositions were analysed by confocal Raman microscopy regarding MPT distribution within the imprinted ODFs. Adjusted print settings, speed, print direction and angle, characterised the final ODF surface structure. The present investigations show that uniform dosages with acceptance values between 1 and 6 can be achieved. Nevertheless, changes in calibrated printed quantity due to nozzle aging have a significant effect on the final applied dose. At the lowest investigated quantity, the RSD was ±28% and at the highest, ±9%. This has to be considered for implementation of inkjet printing as a pharmaceutical production tool in the future.